Analisis Instrumen Evaluasi Keterampilan Menyimak Bahasa Arab pada Platform Alef - Suci Kirani Adhistia; Hikmah; Masrun (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
This study aims to analyze the evaluation instruments for Arabic listening skills in the Alef application. The research method used is descriptive qualitative with a content analysis approach. Data was collected through in-depth observations of the evaluation features in the Alef application, particularly in the aspect of listening skills (maharah istima'). The research findings show that the evaluation instruments in the Alef application include several important components, namely: (1) the compatibility of materials with user proficiency levels, (2) variations in evaluation question formats including multiple choice, matching, and sentence completion, (3) the quality of audio used in listening tests, and (4) an automatic scoring system that provides immediate feedback to users. However, several limitations were found, such as the lack of variation in question difficulty levels and the absence of assessment for advanced listening skills. This research provides recommendations for developing more comprehensive evaluation instruments in technology-based language learning applications.